(untitled) (International Journal of Health, Animal Science and Food Safety, 2017)
Abstract Introductions Aim of EDEN 2020 project’s Milestone 5 is the development of a steerable catheter for CED system in glioblastoma therapy. The VET group is involved in realization and validation of the proper animal model. Materials and methods In this part of the study two fresh sheep’s head from the local slaughter were used. The heads were located into an ad hoc Frame system based on anatomical measures and CT images, producted by Renishaw plc partner in this project. The frame was adapted and every components were checked for the ex vivo validation tests. CT imaging was taken in Lodi at Università degli studi di Milano, Facoltà di Medicina Veterinaria, with CT scanner and MRI imaging was taken in La Cittadina, Cremona Results System validation was approved by the ex vivo trial. The frame system doesn’t compromise the imaging acquisition in MRI and CT systems. Every system components are functional to their aims. Discussion The Frame system is adapted to the sheep head. It is composed by elements able to lock the head during the imaging acquisition. Frame system is characterized by a support base helpings the animals to keep the head straight forward during imaging time, under general anesthesia. The design of these device support the airways anatomy, avoiding damaging or obstruction of airflows during anesthesia period. The role of elements like mouth bar and ovine head pins is to lock the head in a stable position during imaging acquisition; fixing is guaranteed by V shape head pins, that are arranged against the zygomatic arches. Lateral compression forces to the cranium, and the V shape pins avoid the vertical shifting of the head and any kind of rotations. (fig. 1)